2016
DOI: 10.1007/s00228-016-2022-4
|View full text |Cite
|
Sign up to set email alerts
|

Hospital re-admission associated with adverse drug reactions in patients over the age of 65 years

Abstract: This study shows an estimated rate of re-admission for an ADR around 87/1000 within 1 year, and the same drug combination were the suspected cause of repeat admission in half the cases. At least, 11 % of cases were avoidable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 24 publications
0
37
0
1
Order By: Relevance
“…Of the 19 studies, 9 measured DRP‐related readmissions, 7 measured ADRs, 2 measured ADEs, and 1 measured readmissions due to drug‐drug interactions . No study specifically examined readmissions due to MEs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 19 studies, 9 measured DRP‐related readmissions, 7 measured ADRs, 2 measured ADEs, and 1 measured readmissions due to drug‐drug interactions . No study specifically examined readmissions due to MEs.…”
Section: Resultsmentioning
confidence: 99%
“…Good similarity was observed between the reviewers for screening (interrater agreement: κ = 0.78). Of the 19 studies, 17 (89%) were observational, including 11 retrospective studies, 4 prospective studies, and 2 case‐control studies . The remaining 2 studies were a randomized controlled trial and a before‐after study (Appendix ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies that have identified medication-related hospitalizations have relied on clinician review of medical charts and used variable and subjective criteria. [4][5][6][7] Future research should use the Naranjo algorithm with clinician chart review to determine whether a collaborative interprofessional practice model affects the rate of medication-related ED visits and hospitalizations.…”
mentioning
confidence: 99%